Estudo teórico da reatividade de ésteres de fosfato em fase gasosa e em solução aquosa - Eufrasia de Sousa Pereira (2014)
This study investigated the cleavage of P-OC2H5 bond in phosphate esters, dianionic monoethyl phosphate [H5C2OPO32-], monoanionic diethyl phosphate [(H5C2O)2PO2-] and neutral triethyl phosphate [(H5C2O)3PO], with attack of hydroxide ion to the phosphorus atom in aqueous solution and in gaseous phase. This study was conducted using a hybrid quantum mechanical/effective fragment potential (QM/EFP). Structures, energetic properties, reaction mechanism, and the charge distribution along the reaction coordinate were explored. The data were obtained at B3LYP/6-31+G(d,p)/EFP level of theory. The results show that cleavage of the P-OC2H5 bond in the dianionic monoethyl phosphate occurs by way of a dissociative concerted mechanism with activation energy of about 31kcal/mol, which corresponds to a satisfactory agreement with the experimental value of 40 kcal/mol. In more substituted phosphate esters the cleavage occurs in two steps and through an associative mechanism. The first stage of the reaction corresponds to the nucleophilic attack of OH- and formation of a pentacoordinated intermediate, then the determining step of the reaction is the P-OC2H5 cleavage, with free energy of activation of 33 kcal/mol at the B3LYP/6-31++ G (d,p)/EFP level of theory. The experimental value is estimated at 32 kcal/mol, in good agrément with the theorical, showing the effectiveness of the computational methodoly. For the phosphate triester, the calculated activation energy for the rate determining step of the reaction at the same level of theory used for the other esters is 10,4 kcal/mol. The calculated charge distribution along the reaction coordinate shows a small charge transfer from the nucleophile to the phosphorus atom. The nature of P-O interactions was investigated based on the formalism of quantum theory of atoms in molecules (QTAIM) and also using the decomposition of the interaction energy (EDA). The analysis of the local properties ((r), [delta IND. 2] , G(r), V(r) e H(r)) calculated at the critical point P--OH bond (along the reaction coordinate) in conjunction with the analysis of the main components of the interaction energy calculated based on the EDA approach indicated that the formation of P-OH bond in the esters studied is mainly governed by electrostatic contributions.